The Influence of Product Quality and Price Perception on Purchase Decision of Kopi Kelana - Fawwaz Hidayat, Anindya Benita; Kusuma Wardhani, Nuruni Ika (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the influence of product quality and price perception on purchase decisions for Kopi Kelana, amid the increasing competition in the local coffee industry. Using a quantitative method with a survey approach, data were collected from 128 respondents in Surabaya who had previously purchased Kopi Kelana, through an online questionnaire. The analysis was conducted using Partial Least Square (PLS) with the help of SmartPLS software. The results show that both product quality and price perception have a positive and significant effect on purchase decisions. These findings suggest that consumers are more likely to make a purchase when they perceive the coffee as high quality and the price as fair and aligned with the value offered. The implication for Kopi Kelana is the importance of consistently maintaining product quality and implementing a pricing strategy that reflects the perceived value. This research also opens opportunities for further studies by including additional factors such as promotion or customer service.